Combined Surgical Approaches In and Around the Orbit - Stefko, S. Tonya (Journal of Neurological Surgery Part B: Skull Base, 2020)
Orbital pathology requiring surgery can be planned based on the nature of the disease and the position of this relative to the globe and optic nerve complex. Multidisciplinary treatment is now common, and this sometimes includes multiple surgical corridors employed for approach. The orbit is also now frequently used as a corridor to intracranial pathology, and these same processes may be applied. Combined surgical approaches, whether at the same time or staged, allow for minimization of manipulation of critical neurovascular structures in complex skull base pathology.
Keywords: orbit; abscess; tumor; meningioma; cavernous hemangioma; endoscopic; optic nerve